Enhancing dairy production and productivity in Burundi through improved dairy cattle breeds - International Livestock Research Institute (International Livestock Research Institute, 2022)
n this film farmers in Burundi’s Cibitoke, Bubanza, Bujumbura, Rumonge, and Makamba provinces share how their lives have changed following the receipt of Friesian crossbred dairy cows from the regional integrated agricultural development in the great lakes (PRDAIGL) project. Technicians of the National Veterinary Laboratory of Burundi also share how efficiency of carrying out PCR tests has improved with the Applied Biosystems real-time PCR machine donated by ILRI through PRDAIGL.